Character Education For Contemporary Urban Muslim Students: A Comparative Study at UII and UMY Student Islamic Boarding Schools - Syaifulloh Yusuf; Marhumah Marhumah; Aziz Muslim; Nurkhamimi Zainuddin (IAIN Metro Lampung, 2025)
Non-Indexed Publication